Preparation of morselised bone for impaction grafting using a blender method. (February 2018) - Ruddy, Mark; FitzPatrick, David P.; Stanton, Kenneth T.
Abstract: Impaction bone grafting is a method of restoring bone stock to patients suffering significant bone loss due to revision total hip surgery. The procedure requires morselised bone (MB) to be impacted into the site of bone loss in order to stabilise the prosthesis with the aim of the long term resorption and reintegration of the impacted bone graft. Currently, the method for producing MB requires the use of expensive surgical bone mills or manually-intensive rongeurs that can produce a limited variety of particle sizes and may have a low throughput. This study examines the potential to produce suitable MB using a domestic blender. The method produces a wide range of particle sizes without the need for an adjustment of the system. It was found through packing modelling that this particle distribution resulted in reduced initial graft porosity and thus a theoretical potential to increase the graft stiffness and ability of the graft to stabilise a prosthesis in comparison to a manually prepared roughly cut morselised bone samples. Mechanical testing confirmed the increased mechanical performance of the graft through both impaction testing and subsidence testing. The blended MB was found to exhibit greater graft stiffness under the same impaction conditions. The graft was also found to have subsided less in comparison to the rough cut, less well graded MB. Scanning electron imaging also confirmed the retention of the trabecular structure necessary for revascularisation and host bone ingrowth. In conclusion, the blender method offers a rapid and cheap way of obtaining morselised bone with favourable particle size distribution, particle morphology and mechanical properties with preservation of the bone trabecular structure.